Prior knowledge of final testing improves sensorimotor learning through self-scheduled practice - Bastos, F.; Marinovic, Welber; de Rugy, A.; Tani, G. (Elsevier BV; North Holland, 2013)
The elaboration of learning strategies has been considered a key factor to explain sensorimotor learning gains obtained in self-scheduled practice conditions. Nevertheless, the effect of prior knowledge of the testing context (i.e., the learning goal) on that process has been neglected. This study sought to determine whether: (a) learners in a self-controlled condition make different choices contingent on having or not having a learning goal; (b) providing a learning goal would modify the effects of a self-controlled practice condition, and (c) the effect of providing a learning goal would be due to the augmented cognitive effort or to the practice schedule resulting from the learning strategies. The results show that prior knowledge of a variable testing context affects the elaboration of learning strategies and improves skill acquisition in a self-scheduled practice condition. Furthermore, learning gains can be attributed to the self-imposed practice schedule resulting from the learning strategies, and not to the process of elaborating them.